Effects of Matrix Creep Properties on Effective Irradiation Swelling of U-10Mo/Zr Dispersion Nuclear Fuels - Li, Yong; Zhang, Jing; Jian, Xiaobin; Yan, Feng; Ding, Shurong; Li, Yuanming (Frontiers in Energy Research, 2022)
A meso-mechanical model is established for the homogenized irradiation swelling of U-10Mo/Zr dispersion fuels, with an equivalent sphere chosen as the representative volume element (RVE). In the simulation, a mechanistic model for the fission gas swelling of U-10Mo particles and the creep model for Zr matrix with different values of the creep amplification factor are included. Based on the developed method, the results of effective irradiation swelling of U-10Mo/Zr dispersion fuels are obtained by finite element simulation. Additionally, the effects of matrix creep properties on the effective irradiation swelling are investigated. The numerical results indicate that 1) the Zr matrix has the function of restraining and compensating the irradiation swelling of fuel particles by the mechanical interactions between the fuel particles and the matrix; 2) with the increase in the creep amplification factor of the matrix, the effective irradiation swelling increases while the stresses in the fuel particles and the matrix decrease. The enhanced creep rate of the matrix is apt to result in less restraint of the effective irradiation swelling, but reduces the risk of radial crack initiation and propagation in the matrix; 3) based on the results of finite element simulation, a mathematic model for the effective irradiation swelling of U-10Mo/Zr dispersion fuels is fitted to correlate the effective irradiation swelling with different values of the matrix creep amplification factor under the considered irradiation conditions. The creep property of the matrix should be optimized because of its evident effects on the effective irradiation swelling and stresses of the U-10Mo/Zr dispersion fuels.